Effect of Andrographolide on Gene Expression Profile and Intracellular Calcium in Primary Rat Myocardium Microvascular Endothelial Cells. Issue 6 (December 2017) - Feng, Bo; Zhang, Qian; Wang, Xin; Sun, Xiangwan; Mu, Xiang; Dong, Hong
Abstract : Abstract: Andrographolide (ANDRO) is a diterpene lactone compound with extensive biological effects, such as antibacterial, antitumor and treatment of cardiovascular diseases. Until now, studies on the pharmacological functions of ANDRO are still in progress. However, little is known about the gene expression profile and calcium response of endothelial cells to ANDRO. In this study, we used a microarray technology to investigate the gene expression responses in primary rat myocardium microvascular endothelial cells treated with 10 μg/mL ANDRO. The expression of caveolin-1 and 1-phosphatidylinositol 4, 5-bisphosphate phosphodiesterase δ3 was verified by RT-PCR and western blot. In addition, we investigated the effect of ANDRO on intracellular calcium induced by exogenous adenosine triphosphate and on inflammatory response induced by lipopolysaccharide. Results showed that ANDRO treatment induced an abundance of differential expressed genes, exhibiting a multitarget regulatory effect. ANDRO significantly decreased caveolin-1 and phosphodiesterase δ3 expression, lipopolysaccharide-induced IL-6 and TNF-α levels and expression of several chemokine genes, which are associated with reducing inflammation response and decreasing calcium release without affecting normal endothelia cell function, suggesting that ANDRO may be a potential candidate to treat cardiovascular diseases with less toxicity. Abstract : Supplemental Digital Content is Available in the Text.